Improving Workshop Learning Outcomes With Practical Learning Methods - Susilowati Susilowati; Diana Evawati; Umi Nurasiyah; Siti Halimah (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
This study aims to determine the results of the implementation of learning by teachers, to determine student activities obtained when students take part in the learning process, and to determine students' cognitive learning outcomes. One of the workshops learning in SLTP consists of culinary which some students have difficulty in learning. For this reason, it is necessary to choose the right teaching method to facilitate students learning. Practical learning is one of the alternatives that can improve student learning outcomes. The research method carried out by PTK with two research cycles, each cycle consists of 4 (four) stages, namely planning, action, observation, and reflection, while the data collection technique is giving pre-tests and post-tests consisting of three questions. The results showed that practicum learning can improve the learning outcomes of culinary crafts on the subject of cold and hot drinks in class VIII UPT SMP Negeri 1 Palang. This is evidenced by the initial test before the action was taken, which was an average of 64, cycle I obtained an average score of 71.39, in this case reaching 77.78% and cycle II obtained an average score of 83 in other words reaching 97.22%. So, in the actions of cycle I and cycle II there was an increase of 20.56%. So that PTK is declared successful and complete.